2021
DOI: 10.1186/s12905-021-01411-4
|View full text |Cite
|
Sign up to set email alerts
|

Women’s decision-making power in a context of free reproductive healthcare and family planning in rural Burkina Faso

Abstract: Background In 2016, the national user fee exemption policy for women and children under five was introduced in Burkina Faso. It covers most reproductive healthcare services for women including prenatal care, delivery, and postnatal care. In subsequent years, the policy was gradually extended to include family planning. While studies have shown that user fee abolition policies increase visits to health centers and improve access to reproductive healthcare and family planning, there are also indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
5
11
0
Order By: Relevance
“…On the contrary, the COVID-19 pandemic likely contributed to the increase in contraceptive use in the panel, from 41% in February 2020 to 50% one year later. It is worth noting that Burkina Faso has implemented several interventions to increase access to family planning services over the last few years, notably by removing user fees for contraception and for postnatal visits [39]. The upward trend in contraceptive use has been steady and rapid since 2015; that year, the contraceptive prevalence rates in the Cascades and Centre-Ouest regions (where the study area is PLOS GLOBAL PUBLIC HEALTH located) were estimated to be 21% and 28%, respectively, while the national prevalence of unmet need for family planning reached 35% [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the COVID-19 pandemic likely contributed to the increase in contraceptive use in the panel, from 41% in February 2020 to 50% one year later. It is worth noting that Burkina Faso has implemented several interventions to increase access to family planning services over the last few years, notably by removing user fees for contraception and for postnatal visits [39]. The upward trend in contraceptive use has been steady and rapid since 2015; that year, the contraceptive prevalence rates in the Cascades and Centre-Ouest regions (where the study area is PLOS GLOBAL PUBLIC HEALTH located) were estimated to be 21% and 28%, respectively, while the national prevalence of unmet need for family planning reached 35% [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that women's sole decision-making does not necessarily improve with the provision of free or subsidized healthcare. Findings from Burkina Faso stated that even in the context of free maternal healthcare, husbands' authorization was still necessary for using maternal healthcare and women were deemed stubborn or domineering if they ventured on healthcare decisions alone ( 50 ). Interestingly, the study revealed that joint decision-making among couples was the most acceptable health-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the policy has facilitated access to FP services, but previous literature suggests that user fee removal policies alone does not necessarily suggest increased women’s decision-making autonomy regarding FP [ 30 ]. Another study conducted in Burkina Faso after the removal of user fees for FP services reported increased marital tension [ 31 ]. In some instances, healthcare providers had to adapt their practices to guarantee women’s confidentiality and safety [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Burkina Faso after the removal of user fees for FP services reported increased marital tension [ 31 ]. In some instances, healthcare providers had to adapt their practices to guarantee women’s confidentiality and safety [ 31 ].…”
Section: Discussionmentioning
confidence: 99%